47 Using Natriuretic Peptide Levels to Diagnose Heart Failure in Primary Care: An Evaluation of the 2010 United Kingdom National Institute of Clinical Excellence Guidelines on the Diagnosis of Chronic Heart Failure. (6th June 2015) - Jamil, Haqeel; Gierula, John; Byrom, Rowenna; WInsor, Sarah; Sunley, Emma; Kearney, Lorraine; Houghton, Anne; Bailey, Kristian; Cubbon, Richard; Reynolds, Gregory; Pavitt, Sue; David, Cairns; et al.
Abstract : Introduction: Chronic heart failure (HF) due to left ventricular systolic dysfunction (LVSD) is common and associated with high morbidity and mortality. The 2010 UK National Institute for Health and Care Excellence (NICE) guideline (CG-108) advises the measurement of natriuretic peptides (NP) in patients presenting to primary care with symptoms possibly due to HF without previous myocardial infarction (MI); with elevated concentrations triggering referral to a HF clinic. The aim of this study was to describe the results of implementation of the 2010 NP-based diagnostic guidelines for HF. Methods: We prospectively collected demographic data from all patients in Leeds who underwent an NP test between 1 st May 2012 and 1 st May 2013. In those referred to the Leeds Integrated HF Service we collected clinical variables, electrocardiography and echocardiography data. Results: Of the 4415 NT-pro-B-type NP tests performed in the twelve months to May 1 st 2013, 543 (12%) returned a 'high' result (>2000 ng/L), and 1067 (24%) an 'intermediate' result (400–2000 ng/L). Of 1610 patients with an elevated result and no previous MI, 820 (51%) were referred to secondary care. Patients with a previous MI or a 'high' result were more likely to have LVSD (83/173, 48% and 131/245, 53% respectively), than those with 'intermediate' concentrations (112/447, 25%). Overall, the yield from 4263 NP tests (in patients without a previous MI) was 243 new diagnoses of LVSD. Conclusion: Comprehensive implementation of the 2010 NICE guidelines for the diagnosis and management of HF has led to a large number of NT-pro-BNP tests and few new diagnoses.